The Effectiveness of Audio Visual Media in Reporting Technique Material in Improving Accounting Economics Learning Outcomes for Class Students at SMAN 2 Majene - Aulia. M, Siti; Lannai , Darwis; Kalsum, Ummu (Westscience Press, 2024)
This study examines the impact of leadership style, organizational culture, policy implementation, and community participation on the efficiency of public services and the happiness of employees in local government in Indonesia. The study involves a quantitative analysis with a sample size of 250 participants. It utilizes a Likert scale ranging from 1 to 5 and leverages Structural Equation Modeling-Partial Least Squares (SEM-PLS 3) for data analysis. The findings demonstrate that all connections are both positive and statistically significant, emphasizing the crucial functions these parameters fulfill in public administration. Leadership style, corporate culture, policy execution, and community participation have a major positive impact on both public service efficiency and employee happiness. The findings provide significant theoretical contributions to the comprehension of public sector management and present practical implications for policymakers and practitioners seeking to enhance public service performance and employee morale.